Effects of China's Structural Change on the Exports of East Asian Economies. Issue 3 (May 2017) - Lee, Hyun‐Hoon; Park, Donghyun; Shin, Kwanho
Abstract: The Chinese economy is slowing down and is in the midst of a structural transformation from export‐led and investment‐led growth to domestic demand‐led and consumption‐led growth. While there are widespread concerns among China's trading partners about the effect of the slowdown in China's growth on their exports, China's structural changes are also likely to have a significant impact: for example, China will import fewer machines and more cosmetics. The central objective of the present paper is to empirically examine the effect of China's structural transformation on the exports of East Asian economies, which have close trade linkages with China. We find that economies that have failed to increase the share of consumption goods in their exports to China have suffered larger declines in their quantities of exports to China. In addition, economies that have suffered losses in their shares of China's parts and components imports have faced reductions in their shares in China's total imports.